High-speed rail: will it change the dynamics of US intercity passenger travel?. (1st January 2013) - Williams, Michael J.; Rhoades, Dawna L.; Simms, Thomas A.
As both the skies and highways become more crowded, travellers continue to look for cheaper and efficient alternatives. The National Railroad Passenger Corporation, commonly known as Amtrak, faces increased pressure to meet this need. Notorious for failing to meet on-time standards as well as operating consistently at a loss, discussions of the implementation of high-speed rail (HSR) projects has caused increased optimism in the future of US intercity passenger rail. This study reports on research conducted in 2009 comparing US air carriers and highway travel with current Amtrak service. A discussion of HSR is included with an examination of the effects it could have on intercity transportation. Our conclusion is that Amtrak continues to compete ineffectively despite an increase in popularity and any introduction of HSR will require significant changes to current intercity rail travel system.